Harnessing The AAOIFI Transaction Standard for Halal Digital Entrepreneurship Engagement: Empirical Evidence from Indonesian Entrepreneurship - Arifin, Afrad; Ginting, Henndy; Rahadi, Raden Aswin; Hidayat, Sutan Emir (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2024)
Abstract. Halal entrepreneurship is relevant for national economic growth, with the application of the AAOIFI transaction standard (ATS) having diverse impacts on halal digital entrepreneurship engagement. Despite the significant halal market value, ATS influence on business practices presents significant opportunities and challenges for halal digital entrepreneurship engagement, particularly in Indonesia. This qualitative study investigates the relevance and applicability of ATS in Indonesia’s halal digital entrepreneurship engagements through 13 purposive sampling semi-structured interviews analyzed thematically (open coding and axial coding) using NVIVO software. Findings accompanied by negative cases highlight the practical theme of strategic engagement and application of the ATS, contributing new perspectives to halal entrepreneurship theory and practice in halal digital business that harnesses the ATS. This theoretical implication extends the understanding of halal digital entrepreneurship and conforms to the importance of integrating AAOIFI into the halal ecosystem. Practical implications include leveraging ATS for digital business growth while upholding Islamic values, extending ATS application to the real sector, both globally and digitally, and understanding ATS as crucial for success in halal digital businesses. Keywords: Halal entrepreneurship, entrepreneurship engagement, AAOIFI transaction standard, Indonesia’s halal digital business, thematic analysis